ANALYSIS OF ACTIVATED CARBON (PETUNG BAMBOO)/LATEX COMPOSITE AS X-BAND WAVE-ABSORBING MATERIAL - Khoirotun Nadiyyah; Dwi Wahyu Hardiyanto; Dwi Irma Aprilia; Rizky Firmansyah; Nurul Amaliya Triyuliana; M. Zainuri (JOURNAL ONLINE OF PHYSICS, 2023)
In maintaining the sovereignty of a country, especially in border regions was needed defense tools that had the latest technology, such as stealth technology. Stealth technology was applied to military ships or aircraft so that they could not be detected by Radio Detection and Ranging. Stealth technology in this research was realized by coating the ship's or aircraft's body using RAM (Radar Absorbing Material). RAM could be composed of dielectric materials, such as activated carbon. The activated carbon was synthesized from Dendrocalamus Asper. This research aimed to analyze the proper of composition the composite and thickness of the RAM for the X-band wave range. The methods were carbonization, activation by KOH and HCl solutions, and characterization. The characterizations were by XRD, FTIR, and SEM to identify the active carbon phase, and VNA to determine the value of reflection loss. The variations in this research were composite composition (7:3, 9:1) and thickness (1mm, 3mm). And obtained that it has been formed a composite of activated carbon of petung bamboo and latex of rubber tree, which is indicated by the formation of two broad peaks in the diffraction pattern, the presence of band groups C=C, C-C, C-H, C-O, O-H, and morphology with a porous structure. In addition, the highest reflection loss is obtained for the 9:1 composite and thickness of 3 mm, which reached -17.25 dB at a frequency of 9.32 GHz.